Pengaruh Pemberian Apu-Apu (Pistia Stratiotes L) Sebagaipupuk Organik dengan Dosis yang Berbeda terhadap Populasi Kutu Air ( Daphnia Sp ) - Tania Serezova Augusta (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Water flea or Latin (Daphnia sp) is one type of natural food that is very important for natural fish feed. But these water fleas are very rare to find if not cultivated, especially in fresh water. This condition causes water fleas to be limited and need to be cultivated. This study aims to determine the effect of apu-apu (Pistia stratiotes l) as an organic fertilizer with different doses of water flea population (Daphnia sp). Usefulness of the research to provide information on the effects of apu-apu (Pistia stratiotes l) as organic fertilizer with different doses of the water flea population (daphnia sp). This research was conducted for two weeks starting from 02 - 17 May 2017. The research was conducted in the Laboratory of the Faculty of Fisheries of Palangka Raya Christian University. With the implementation method are: preparation of 9 (nine) aquarium for cultivation media of Daphnia sp, making of organic fertilizer, giving different dose respectively: treatment A: 0,25 gr / ltr water, treatment B: 0,50 gr / ltr water, C: 0.75 gr / ltr water treatment, and water quality observation. The results showed that the dosage of apu-apu (0,25) gr / ltr water, (0,50) gr / ltr water and (0,75) gr / ltr of water had a significant effect on the water flea population. Based on further experimental test of significant difference (BNT) with 99% confidence level, showed treatment A dose 0,25 gr / ltr water better than treatment B dose 0,50 gr / ltr water and treatment C 0,75 gr / ltr water and 0.5 gr / ltr water treatment is better than 0.75 g / ltr water. The average of water quality conditions in the maintenance of water fleas in Aquarium are DO = 5,23-5,29 ml / l, pH = 6,43-7,55, Temperature = 26,34- 26,56 C, TDS = 52,33-60.99 ml / l. Water quality parameters strongly support the presence of water flea population.